EXPERIENCES OF MAINSTREAMING GENDER PERSPECTIVES: The case of the Faculty of Engineering at UNLZ, Argentina, 2019-2023 (Journal of Industrial and Mechanical Engineering, 2024)
The recent implementation of public policies with a gender and human rights perspective has generated tensions and conflicts by showing violent practices in institutions. There is still resistance to new initiatives in the university environment, especially in engineering, where systems of prerogatives and practices that reinforce male authority dominate. Various literature defines gender mainstreaming as the systemic integration of gender inequality into institutional policies. This work explores the mainstreaming strategies implemented in the UNLZ Faculty of Engineering (2019-2023), covering training, awareness, research, extension, linkage, and regulatory development.
Keywords: Universities; Engineering; Mainstreaming; genders; Diversity